Redirecting innovation in U.S. Health care : options to decrease spending and increase value - Garber, Steven, 1950-; Gates, Susan M., 1968-; Keeler, Emmett B.; Vaiana, Mary E.; Mulcahy, Andrew; Lau, Christopher; Kellermann, Arthur L.; Rand eBooks (Santa Monica, CA : RAND, 2014)
New medical technologies are a leading driver of U.S. health care spending. This report identifies promising policy options to change which medical technologies are created, with two related policy goals: (1) Reduce total health care spending with the smallest possible loss of health benefits, and (2) ensure that new medical products that increase spending are accompanied by health benefits that are worth the spending increases. The analysis synthesized information from peer-reviewed and other literature, a panel of technical advisors convened for the project, and 50 one-on-one expert interviews. The authors also conducted case studies of eight medical products. The following features of the U.S. health care environment tend to increase spending without also conferring major health benefits: lack of basic scientific knowledge about some disease processes, costs and risks of U.S. Food and Drug Administration (FDA) approval, limited rewards for medical products that could lower spending, treatment creep, and the medical arms race. The authors identified ten policy options that would help advance the two policy goals. Five would do so by reducing the costs and/or risks of invention and obtaining FDA approval: (1) Enable more creativity in funding basic science, (2) offer prizes for inventions, (3) buy out patents, (4) establish a public-interest investment fund, and (5) expedite FDA reviews and approvals. The other five options would do so by increasing market rewards for products: (1) Reform Medicare payment policies, (2) reform Medicare coverage policies, (3) coordinate FDA approval and Centers for Medicare & Medicaid Services coverage processes, (4) increase demand for technologies that decrease spending, and (5) produce more and more-timely technology assessments.
Introduction -- The Context for Medical Product Innovation -- Methods -- Analysis -- Policy Options to Improve the U.S. Medical Product Innovation System -- In Conclusion -- Appendix A: Cost-Effectiveness and Value -- Appendix B: An Economic Model of Innovation.
"RAND Health."
Includes bibliographical references (p. 91-105).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Electronic books